Pengaruh Strategi Green Marketing terhadap Kepuasan Pelanggan pada produk The Body Shop - Adsuni, Nur Aini; Lu, Cen (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to analyze the effect of green marketing strategies on customer satisfaction with The Body Shop products. Green marketing includes aspects of product, price, promotion, and place that focus on environmental sustainability. This data was analyzed using quantitative methods with simple linear regression tests, totaling 120 respondents with X variable (customer satisfaction) and Y variable (green marketing). The results of this study indicate that green marketing strategies have a significant effect on customer satisfaction. Factors such as environmentally friendly packaging, packaging recycling campaigns, and strategic locations play an important role in creating added value for consumers. This research suggests expanding sustainability programs through cooperation with local communities and environmental organizations to expand the company's social impact